ANATOMICAL STUDY OF NUTRIENT FORAMINA IN LONG BONES OF HUMAN UPPER AND LOWER LIMBS - BR, PADMASHREE; SHANKAR, VEENA VIDYA; SHETTY, SHAILAJA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study are as follows: (1) To determine the number, location, position, and direction of nutrient foramina in the shaft of long bones. (2) To determine the foraminal index of the long bones. Methods: This was a cross-sectional study, undertaken on dry cadaveric human long bones of unknown age and sex from the Department of Anatomy, M.S. Ramaiah Medical College, Bangalore. The duration of study was 2 years. In this study, 350 human long bones which include the clavicle, humerus, radius, and ulna from the upper extremity; femur, tibia, and fibula from the lower extremity were examined in detail for the number, position, location, and directions of the nutrient foramen. For statistical purposes, p<0.05 was taken as significant. Results: All the bones had single nutrient foramina and a higher percentage of double nutrient foramina was seen in femur. The most common position was the middle one-third of the shaft and the surface distribution was different in different bones. All the bones had the nutrient foramina, which were directed away from the growing end. The mean foraminal index for clavicle, humerus, radius, and ulna was 52.85±9.24, 56.92±6.57, 34.80±6.07, and 36.0±5.85, respectively. Mean foraminal index for femur, tibia, and fibula was 43.54±10.32, 32.37±3.1, and 51.68±9.77. Conclusion: Knowledge of nutrient foramina of long bones is crucial for orthopedic surgery, forensic identification, obtaining vascularized bone grafts, and treating trauma or malignant bone conditions.